2012
DOI: 10.1245/s10434-012-2523-z
|View full text |Cite
|
Sign up to set email alerts
|

Changing Behavior in Clinical Practice in Response to the ACOSOG Z0011 Trial: A Survey of the American Society of Breast Surgeons

Abstract: ACOSOG Z0011 has changed surgical practice. ASBrS respondents have embraced Z0011 and have changed their practice, omitting ALND in patients with one or two positive SLNs who will undergo WBI. However, many also omit ALND in patients undergoing surgery without radiation or with APBI. As these clinical scenarios were not studied in Z0011, further evaluation is required prior to changing clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
40
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(43 citation statements)
references
References 27 publications
3
40
0
Order By: Relevance
“…3,13 These findings have dramatically changed surgical practice, with more than half of all American surgeons, who were surveyed in 2012, stating that they had omitted ALND for patients who met Z0011 criteria. 11 Such a major shift in surgical practice has likely had an impact on most pathology practices as well.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…3,13 These findings have dramatically changed surgical practice, with more than half of all American surgeons, who were surveyed in 2012, stating that they had omitted ALND for patients who met Z0011 criteria. 11 Such a major shift in surgical practice has likely had an impact on most pathology practices as well.…”
Section: Commentmentioning
confidence: 99%
“…9 Although the ASCO guidelines provide an online appendix addressing pathologic evaluation of SLNB and known limitations of frozen section diagnosis, the guidelines do not encourage or discourage the use of frozen section diagnosis for SLNB. 8 Although much has been published regarding changes in surgical practice since Z0011, 5,6,[10][11][12] to our knowledge this is the first study to acknowledge Z0011's effect on pathology practice. Prior to the published Z0011 trial results, the vast majority of SLNBs were sent for frozen section diagnosis at our institution.…”
mentioning
confidence: 99%
“…10,11 Survey studies indicate a shift in thought regarding approach to the axilla following Z0011. 12,13 Other studies have examined the hypothetical impact of applying the study criteria across different populations. [14][15][16] Despite these findings, only one study from MD Anderson Cancer Center has been published to date evaluating the actual impact of this study on clinical practice.…”
mentioning
confidence: 99%
“…Recent studies have suggested that patients with micro-metastatic SLN can avoid complete nodal dissection (5–7). By contrast, a conservative surgical approach of patients with macrometastatic SLN is highly debated and still unaddressed (8–10). Great effort is thus requested to pathologists in the evaluation and quantification of the tumor burden in SLN.…”
Section: Introductionmentioning
confidence: 99%